2018
DOI: 10.1186/s12906-018-2310-x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the main components and bioactivity of Rhus verniciflua Stokes extracts by different detoxification processing methods

Abstract: BackgroundRhus verniciflua Stokes is an Asian tree species that is used as a food supplement and traditional medicine in Korea. However, its use is restricted by its potential to cause allergy. Thus, allergen-free R. verniciflua extracts are currently being marketed as a functional health food in Korea. In the present study, three different allergen-free R. verniciflua extracts (DRVE, FRVE, and FFRVE) were produced by detoxification of R. verniciflua, and their properties and constituents were compared.Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 15 publications
4
15
0
Order By: Relevance
“…Hence, various methods for removing urushiol have been described [22][23][24]. However, several detoxification methods to remove urushiol lead to the loss of bioactive compounds in RV [25]. FRVE is a microbe-detoxified RV, whose anti-hepatic lipidemic effects and bioactive compounds were previously reported by us [5].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, various methods for removing urushiol have been described [22][23][24]. However, several detoxification methods to remove urushiol lead to the loss of bioactive compounds in RV [25]. FRVE is a microbe-detoxified RV, whose anti-hepatic lipidemic effects and bioactive compounds were previously reported by us [5].…”
Section: Introductionmentioning
confidence: 99%
“…Toxicodendron vernicifluum Stokes (TVS) was found to contain a number of bioactive phytochemicals, including alkaloids, polyphenols and flavonoids [12]. Previous research has shown that TVS extract has antioxidant, anti-bacterial, anti-obesity, anti-proliferative, anti-inflammatory, and anti-tumor effects [12][13][14][15][16][17][18][19][20][21][22]. Despite the beneficial pharmacological effects of TVS, its use has been somewhat limited due to the presence of urushiol an allergenic substance, that is a mixture of several derivatives of catechol.…”
Section: Introductionmentioning
confidence: 99%
“…RVS contains numerous useful compounds, such as quercetin, fustin, fisetin, sulfuretin, and butein. Previous research has shown that Rhus verniciflua Stokes extract (RVSE) has antioxidant, anti-proliferative, anti-inflammatory, and anti-tumor effects [ 8 9 10 11 12 13 14 15 16 17 18 ]. Several in vivo and in vitro studies demonstrated antitumor effects of RVSE and/or its compounds in gastric, breast, liver, lymphoma, and osteosarcoma [ 13 19 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the components contained in allergen-free RVSE and their subsequent effects have been shown to differ depending on the specific method of detoxification (removing urushiol). Thus, it is possible to maximize the specific effect by modifying the detoxification method [ 17 ]. We modified the existing extract method to create a new, concentrated and purified allergen-free RVSE.…”
Section: Introductionmentioning
confidence: 99%